Institutionalization of the Restorative Justice Principles in Conflict Resolution Council - Vahedi, Hassan; Zahedi, Abdolvahid (International Journal of Criminology and Sociology, 2022)
Recently, the restorative justice has been considered as a novel method in the legal and criminal system. Attending the restorative justice is directly related to victims’ rights and interests that is often considered as a supplementary way. However, in various legal systems, special attention has been paid to restorative justice and its principles has been recognized in many legal systems, including common law legal system. In Iran, attention and emphasize on the subject of restorative justice do not have a long history. However, currently, in some of the Iranian judicial and legal entities, these principles have been approved. The important subject is to what extent has these principles been institutionalized and approved in these two legal systems. In this paper, an attempt has been made to investigate the position and acceptance and institutionalization amount of the principles of the restorative justice in the conflict resolution council in Iran and similar entities in common law regulations. The findings obtained from the investigations conducted in this context illustrate that in conflict resolution council and their structures, attending the restorative justice has been highlighted. In the theoretical context, too, the principles of restorative justice are adapted to conflict resolution council objectives and tasks.